Economic burden analysis of pediatric tracheobronchial foreign body - Wen-yuan Wang; Tao Zhang; Wan-Yi Li; Shu-Ying Wang; Qi-Jun Zhao; Yong-Jun Wang (Frontiers in Public Health)
ObjectivesTracheobronchial foreign body aspiration (TFBA) constitutes a life-threatening pediatric emergency with substantial clinical and public health implications. While current research prioritizes diagnostic and therapeutic strategies for TFBA, limited attention has been paid to its socioeconomic consequences. This study focuses on Gansu Province, a representative underdeveloped region in China, to systematically assess both direct medical costs (surgical interventions and hospitalization) and broader socioeconomic impacts of pediatric TFBA management. The findings aim to inform evidence-based healthcare policies for childhood emergencies in resource-limited settings.MethodsUsing Gansu Provincial statistical data, we analyzed the economic burden of 951 pediatric tracheobronchial foreign body cases (2017–2021) meeting inclusion criteria at a provincial tertiary hospital’s respiratory department.Results(1) Urban–rural disparities in economic burden: The average annual total income of rural households was significantly lower than that of urban households (p < 0.01). The proportion of hospitalization costs relative to income in rural areas reached 36.31 ± 4.43%, 3.1 times that of urban households (11.91 ± 2.14%, p < 0.001). Rural minority-concentrated regions bore the heaviest burden (48.06%), while urban Han-majority regions had the lowest burden (9.29%). No significant urban–rural difference in surgical costs (P>0.05). (2) Regional heterogeneity in economic burden: Hospitalization costs in underdeveloped minority-concentrated rural areas reached 13,323¥ (8% higher than the rural average), yet their income (27,678¥) was 33% below the average. Their cost-to-income ratio (48.06%) was 3.2 times that of their urban counterparts (15.21%). In developed Han-majority regions, despite comparable hospitalization costs (11,872 ¥ vs. 12,339 ¥), the higher income (42% above average) resulted in the lowest cost-to-income ratio (21.52%).ConclusionTFBA poses a critical global health challenge with disproportionate impacts on children aged 1–3 years and significant economic burden on families, especially in underdeveloped minority-concentrated rural areas. This study highlights severe urban–rural disparities in economic burdens.